HABITUS SISWA DIFABEL DALAM PROSES PEMBELAJARAN DI SLB C-C1 YAKUT PURWOKERTO - Shiddiq, Muhamad Arkan As; Sabrina, Laila; Al Farizi, Muhammad Ghifa; Nurmaulidya, Jasmin Husna; Xielfa, Balqist Maghfira; Haikal, Miko Dwi (Nindikayla Institute, 2023)
This study focuses on the disabled habitus in the learning process at SLB C-C1 Yakut Purwokerto, a special school for children with special needs. The background of this study is to understand how habitus or habits formed from social and educational experiences affect the learning process of students with disabilities, especially mentally disabled. Data from the 2018 National Socio-Economic Survey (Susenas) and the Banyumas Social Service 2020 show a high number of people with disabilities, emphasizing the importance of inclusive and adaptive education. This study used qualitative methods with in-depth interviews with teachers, staff, parents and students at SLB C-C1 Yakut to understand the social interactions and challenges faced in learning. The findings of this study show that each student has different needs and responses in the learning process, requiring a flexible and individualized approach. Challenges such as tantrum behavior and communication difficulties are common, especially in autistic students. This research provides insights into the important role of habitus in supporting effective and inclusive learning for students with disabilities and underscores the need for holistic support from schools, parents and communities. It is hoped that the results of this study can help improve understanding and acceptance of students with disabilities and encourage the implementation of more inclusive and adaptive learning strategies.